E-book educativo para pacientes candidatos a procedimentos minimamente invasivos na face - Menezes, Caio Cezar Oliveira [UNIFESP] (2021)
Introduction: There is an increasing search for minimally invasive procedures on the face. Influenced by digital media, patients see the procedures as banal, seek untrained professionals, and health literacy is essential. Education and the transmission of knowledge is an important strategy in the health area, and the breaking down of knowledge barriers is a tool for social inclusion and improvement of public health. The proven importance of digital media (internet, cell phones and others) in the effectiveness of the transmission of information and knowledge occupies a prominent place in the 21st century, being a comprehensive instrument capable of reaching a large portion of the population quickly and free of charge. In this way, it was understood the need to seek effective means for the population's awareness and education in order to make the patient an active participant in his treatment. Objective: An educational e-book was developed for patients who are candidates for minimally invasive procedures on the face. Method: For the development of the e-book, the “Design Thinking” method was used, divided into four phases (Discover, Define, Develop and Deliver). The content and e-book validation was carried out using the Delphi methodology through the consensus of experts. Result: An educational e-book was developed for patients who are candidates for minimally invasive procedures on the face. Conclusion: An effective means of educating the patient about minimally invasive procedures was made possible with this e-book.